Tribal warfare: Commensal Neisseria kill pathogen Neisseria gonorrhoeae using its DNA - Magdalene So; Maria A. Rendón (Microbial Cell, 2019)
It is now abundantly clear that our microbiota (commensals) are critical for many physiological and developmental processes. They have also been shown to inhibit pathogen colonization, through a variety of means including nutrient competition and secretion of microbicidal or biofilm-inhibiting proteins/peptides. Our recent study, Kim et al., (2019), adds a new dimension to the concept of commensal protection. It shows that commensal Neisseria kill the closely related pathogen N. gonorrhoeae through an unexpected mechanism, one that involves genetic competence, DNA methylation state and recombination. This microreview summarizes the report and discusses questions and lines of research arising from the study. Further investigation into this DNA-based killing mechanism will provide a better understanding of Neisseria biology and commensal-pathogen interactions on the mucosa, and identify strategies for preventing pathogenic Neisseria transmission.